Christian Education in Khulna Bangladesh: Conversion, Community, and Propagated Values - Mahmudul Hasan (Penerbit Hellow Pustaka, 2026)
This research presents an in-depth analysis of the role of Christian missionary education in Khulna, Bangladesh, with a focus on the contribution to the spread of Christianity and its potential impact in the context of a Muslim-majority society. Based on the text of the Gospel of Matthew, this research explains the three main goals of Christian missionary education, namely the conversion of students to Christianity, the formation of a strong Christian community, and the spread of Christian values. Through a careful literature review and in-depth content analysis, this article discusses the types of educational institutions established by Christian missionaries in Khulna, including regular schools, vocational training centers, Christian theological schools, and Christian boarding schools. Emphasis is placed on the nuanced approach used, including the instillation of Christian ideology in the curriculum, the promotion of values such as compassion and social responsibility, and the provision of scholarships to underprivileged individuals. The research also explores the potential impact in Muslim communities, where conversion may be difficult due to cultural and social norms. Although conversion does not always occur, missionary education can contribute to secularization or de-Islamization by influencing society's attitudes and views. Additionally, this article discusses the policy landscape surrounding missionary education in Bangladesh and government efforts to regulate these institutions. In its conclusion, this research provides in-depth insight into the multi-layered approach taken by Christian missionary education in Khulna, as well as its impact on the local community and religious landscape.